The current application of commonly available fruit wastes for the synthesis of polyhydroxyalkanoates from bacteria - Avinash, S.; Aakriti, C.; Mritunjai, S.; Riddhi, T.; Archana, T. (Regulatory Mechanisms in Biosystems, 2025)
The rapid depletion of fossil fuel and its hazardous effect on the environment encourages research on the synthesis of bi o based plastics such as polyhydroxyalkanoates (PHAs) for the replacement of traditional plastics. Polyhydroxyalkanoates (PHA s ) are intracellularly synthesized biopolymer s that are non-toxic and biologically degradable in nature. Their physicochemical and mechanical properties are mostly similar to petrochemically derived plastics. A major limitation of the commercialization of polyhydroxyalkanoates is the high cost in comparison with petroleum-derived polymers. A lot of research is in progress towards searching for the cheapest carbon source for the culture of bacteria. Among various carbon sources available , biosynthesis of PHA from fruit wastes is still in its initial stage and several challenges remain to be resolved. In order to increase the availability of fermentable sugars and increase microbial intake, screening of more fruit waste materials and substrate pre-treatment proc e dures must be improved. For PHA recovery and purification, the development of effective and economical downstream processing methods is an additional area that needs focus. The economic feasibility of PHA manufacturing might be significantly increased by advancements in this area, as these processes now account for a significant amount of the total production cost. The systematic screening of various fruit waste products to determine which ha ve the greatest potential for PHA generation should be the main focus of future studies. Furthermore, improvements in genetic engineering and the optimization of the met a bolic pathways of microorganisms that produce PHA may increase production and lower expenses. This article presents a th o rough analysis of the value-adding of different kinds of fruit wastes for the production of biopolymers, stressing the various strategies used thus far, their drawbacks, and possible future development paths. The large-scale synthesis of PHAs from fruit waste may prove to be a sustainable and profitable way to lessen the environmental effects of conventional plastics by tackling current issues and utilizing cutting-edge technologies.